New low band-gap conjugated organic materials based on fluorene, thiophene and phenylene for photovoltaic applications: Theoretical study. (2016) - Zgou, H.; Boussaidi, S.; Eddiouane, A.; Chaib, H.; Tripathi, R.P.; Ben Hadda, T.; Bouachrine, M.; Hamidi, M.
Abstract: We use the density functional theory (B3LYP/6-31G(d)) to determine structural parameters band gap, absorption and photovoltaic properties of several conjugated organic materials. The chemical structure of these molecules contains fluorene, thiophene and phenylene rings, together with different unities (e.g. Ethylenedioxythiophene EDOT). The theoretical calculations were performed by using Gaussian 09 program supported by GaussView 5.0.8 Interface. The results reveal that the geometrical parameters (dihedral angles, bond lengths) of all molecules possess nearly planar conformations. Moreover, the optoelectronic properties (HOMO, LUMO, Egap…) were determined from the fully optimized structures by using B3LYP/6-31G(d) level. The absorption data (λmax, Etr, OS) of these systems were obtained by TD-B3LYP/6-31G(d) method. The studied molecules Mol-i (with i = 1-6) have low band-gaps with appropriate energy levels of HOMO and LUMO which are desired in photovoltaic applications, especially the Molecules with acceptor unities in their chain. We conclude that these materials are good candidates for bulk heterojunctions used in organic solar cells.